Anti inflammatory Activity of the Ethanol Extract of Cinnamon (Cinnamomum burmannii) Bark using Membrane Stabilization Method and Protein Denaturation - Annisa Shalihah; Fransiska M. Christianty; Fifteen Aprila Fajrin (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Inflammation is the body's reaction to infection, irritation, or foreign substances, as an effort to defend the body's defenses. Inflammatory mediators such as bradykinin, prostaglandins, fluid extravasation, and tissue damage are essential to protect our body as an inflammatory response. One of the plants in Indonesia which is the potential to develop is Cinnamomum burmanii. These plants are identified to contain some substances such as flavonoid, tannin, and saponin. This study was aimed to determine the anti-inflammatory effect of the Cinnamomum burmanii extract using in vitro method compared with diclofenac sodium. Cinnamon bark was extracted using 96% of ethanol, and phytochemical screening was determined. Anti-inflammatory test in vitro using two methods, membrane stabilization using red blood cell suspension and protein denaturation inhibition using bovine serum albumin. After an anti-inflammatory test using the membrane stabilization method, the IC50 of the extract was 84.45 ± 3.55 g/mL, while in the protein denaturation method, the IC50 of the extract was 57.412 ± 0.718µg/mL. Even though the IC50 of the extract was lower, it is still higher than diclofenac sodium as drug control. Our result showed that cinnamon has potential as an antiinflammation and needs to develop further